OPULENCE AND DEFICIT OF ONLINE ACCOUNTING: A PHENOMENOLOGICAL VENTURE - Antonino, Abby Gelle; Burata, Charlot B; Develos, Tristan Evan; Vasquez, Michael B (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Online accounting glimmers in today’s fast-paced society providing businesses with never-before-seen access to real-time financial data and insights. To contextualized this, certified public accounts’ perspectives have to be explored to establish the opulence and even the deficit of the online accounting. This qualitative study investigates the opulence and deficit of online accounting as perceived by certified public accountants (CPAs) in Roxas City establishing its beneficiality, drawbacks, and the perspectives emergent to the lived experiences of CPAs towards this technological shift. The purposively sampled participants – three CPAs in Roxas City - conform to the stipulated inclusion criteria of the study and the framework for phenomenological design regarding the number of the study’s selection. Utilizing a validated semi-structured interview questionnaire, the qualitative data were acquired and thematically analyzed. From the thematic analysis emerged the opulence of online accounting: within the functional performance of the technology being used and within the attitudes of the CPAs themselves. The drawbacks of online accounting stemmed from within the application and within the user. Additionally, the findings highlight a significant shift in the accounting profession towards automation and technology integration, outlining both the strategic advantages and inherent limitations. These results provide an understanding of the evolving landscape of online accounting and the practical implications of online accounting to the accounting practice. Future research studies are still recommended to comprehend deeper the concept of online accounting that can inform strategies to optimize its usage in professional practice.